Peran Wakaf sebagai Penggerak Fasilitas Kesehatan Dalam Peradaban Islam dan Penerapannya di Indonesia - Muhammad Sena Nugraha Pamungkas (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to identify the concept and utilization of waqf in establishing and running health care facilities in Islamic civilization and evaluating if the same concept is applied in Indonesia. By using the documentary research method this study examining and exploring various secondary sources related to the research topic. This research concludes that the use of waqf in supporting and maintaining the sustainability of healthcare facilities has become a part of Islamic civilization. The concept of using waqf in operating and supporting health facilities is also not against the prevailing laws and regulations. In fact, the concept is in the same line with article 170 of Law No. 36 of 2009 concerning Health and Presidential Decree No.59 of 2017 concerning Sustainable Development. With the harmony between the concept of waqf and the prevailing law and regulations, it is expected that the government could realizing development a sustainable and inclusive healthcare facilities based on waqf.